Characteristics of Bioplastic Composites on Variations in Taro Starch (Colocasia esculenta)-Carrageenan Ratio and Polycaprolactone Reinforcing Agent Concentration - Amirrulloh, Muchammad Rizqi; Hartiati, Amna; Suhendra, Lutfi; Arnata, I Wayan (Journal of Fibers and Polymer Composites, 2025)
Using petroleum-based plastics presents significant environmental challenges due to their difficulty in decomposition. This study explores the characteristics of bioplastic composites created from taro starch (Colocasia esculenta) and carrageenan, incorporating polycaprolactone (PCL) as a reinforcing agent. An experimental approach was employed, varying the ratio of taro starch to carrageenan (25:75 and 50:50) and the concentration of PCL (7.5%, 10%, 12.5%, and 15%). The evaluation included tests for tensile strength, elongation at break, elasticity, thickness swelling, and biodegradation. The results showed that the variation of the ratio of taro starch: carrageenan affected tensile strength, elasticity, and biodegradation but not elongation at break and swelling. In comparison, PCL reinforcement affected elongation at break and swelling but not tensile strength, elasticity, and biodegradation. Bioplastic composite with a ratio of taro starch: carrageenan of 25:75 and a concentration of PCL reinforcement of 12.5% ​​(0.75 g) with a tensile strength value of 10.37 ± 2.57 MPa; elongation at break of 2.11 ± 10%; elasticity of 520.07 ± 123.47 MPa; swelling of 70.18 ± 4.96% and the duration of biodegradation on the 5th day. FTIR analysis confirmed the presence of C-H, C-O, C=O, and O-H functional groups, indicating compatibility among the materials in forming the bioplastic composites. The results of this study suggest that bioplastics derived from taro starch and carrageenan, supplemented with PCL, could serve as a promising alternative for environmentally friendly packaging that biodegrades more effectively than traditional plastics.